Malaysian local governments’ role towards sustainable development focusing on knowledge transfer practices framework - Mohamed, Sulzakimin (2014)
Local Governments are facing very demanding and dynamic situation in development agenda when dealing with sustainable development. When the development’s activities do not start with the sustainability elements at Local Governments, the negative impacts are imminent and it will cause hazards to society, economy and environment. Hence, the knowledge of sustainability needs to be inculcated in Local Governments’ practices. It needs to be shown in the stage of planning approval since this is where the development begins. In relation to that, the research objectives are to identify the constraints in knowledge transfer practices of sustainable development in the planning approval at Local Governments, to study the perceptions of stakeholders involved in the planning approval stage at Local Governments regarding knowledge transfer practices towards sustainable development, to study the knowledge transfer practices towards sustainable development at Local Governments and to develop the framework of knowledge transfer practices towards sustainable development into the planning approval stage at Local Governments. Therefore, respondents involved are 55 selected Malaysian Local Governments for questionnaire, 17 selected Malaysian Local Governments for interview and 9 selected stakeholders. The results of this study show that there is lacking in clear direction which bring to the unsupportive policy and management, the perceptions of stakeholders suggest that Local Governments need to show their capabilities in handling sustainable development at the planning approval stage and overall result demonstrates that staffs have low percentage of below 30% in acquiring and participating in activities related to sustainable development. In relation to that, it contributes to the lack of knowledge on sustainable development. Hence knowledge transfer practices towards sustainable development at the planning approval stage are needed as suggested in the analysis of interviews. Therefore, this research has developed a framework of the knowledge transfer practices towards sustainable development at planning approval stage in Malaysian Local Governments, which is to improve the process of the planning approval for sustainability delivery.